Reconceiving the Family : Critique on the American Law Institute’s Principles of the Law of Family Dissolution - Wilson, Robin Fretwell (Cambridge University Press, 2013)
The family has undergone almost revolutionary reconfigurations over the past generation. In the space of a few decades, we have seen the universal recognition in the United States of no-fault divorce, the legal recognition of nonmarital fathers, the establishment of registration schemes and other claims between cohabitants, both heterosexual and homosexual, and the recognition as parents of adults who have neither a biological tie to a child nor an adoptive one.1 Recently, the pace of these changes has become almost frenetic. Just this year, Canada legalized same-sex marriage through national legislation, as South Africa did by judicial opinion